Health Threats by McDonald’s - Khogilavaanni A/P Pathmanathan; Daisy Mui Hung Kee; Sivanesswaren A/L T. Pandiyan Pandiyan; Jeyvendranathan A/L Yuganathan; Pria Nanthini A/P Sivakumaran; Yousef Talal Alrashed (AIBPM Publisher, 2019)
McDonald's is an American fast food company, founded in 1940 as a restaurant operated by Richard and Maurice McDonald, in San Bernardino, California, United States. Currently, McDonald's is the world's largest restaurant chain by revenue, serving over 69 million customers daily in over 100 countries across approximately 36,900 outlets. In 2014, McDonald’s was ranked fifth place 2014 as Most Valuable Global Brand. Based on the online research done, the issues faced by McDonald’s are price sensitivity, increased competition, health threats and many more. The main issue faced by McDonald’s that we are going to focus is the health threats caused by eating McDonald’s. The phrase “fast food” has almost a negative connotation these days. The average McDonald’s meal contains so much of sodium, unhealthy fat, sugar and empty carbs. In fact, the processed fat in McDonald’s foo promotes endothelial dysfunction which is linked to erectile dysfunction down the road. Multiple studies have indicated that eating McDonald’s food could lead to serious health risks such as heart attack, diabetes and high blood pressure. The purpose of this project paper is to analyze the challenges or issues faced by McDonald’s and suggest some business ideas for the company to overcome the challenges. Online research and brainstorming with group members regarding this topic are one of the crucial methods used to collect information regarding this topic. By suggesting a business idea to McDonald’s, it is expected to help McDonald’s overcome this issue quicker.